Perceptions of Shopee and Tokopedia: UMSIDA Management Students' Comparative Analysis: Analisis Komparatif E-commerce Shopee dan Tokopedia: Pandangan Mahasiswa Program Studi Manajemen UMSIDA - Dhinin Bella Ira Sari; Kumara Adji Kusuma (Academia Open, 2023)
This qualitative research with a qualitative descriptive approach aims to explore the views of Management Study Program students at UMSIDA university regarding the ease and benefits of Shopee and Tokopedia e-commerce platforms. Through interviews with 100 students, including 7 informants who were users of both platforms, the research findings indicate that both Shopee and Tokopedia are highly regarded as online shopping sites. Students, being millennials, prioritize convenience and value the extensive product range offered by these platforms. However, the preference of UMSIDA Management Study Program students leans towards Shopee due to perceived affordability and a wider product selection. The implications of this study highlight the significance of user-friendly e-commerce platforms that cater to the needs and preferences of students, thus enabling easy access to online shopping anytime and anywhere. Highlights: Ease and benefits of Shopee and Tokopedia: The research explores the views of Management Study Program students at UMSIDA regarding the convenience and advantages offered by both Shopee and Tokopedia e-commerce platforms. Comparative analysis: The study provides a comparative analysis of Shopee and Tokopedia, highlighting the preferences and opinions of UMSIDA students. It sheds light on factors such as product availability, pricing, and overall user experience. Implications for students and e-commerce platforms: The findings have implications for both students and e-commerce platforms. Students' preferences for Shopee over Tokopedia due to perceived affordability and a wider product range reflect the importance of catering to user needs. E-commerce platforms can use this information to enhance their offerings and improve user satisfaction. Keywords: Shopee, Tokopedia, E-commerce, Management Study Program, UMSIDA